JUAL BELI ONLINE MENURUT PERSPEKTIF ULAMA FIKIH MAJENE - Sukmawati Sukmawati (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2022)
The development of information technology and telecommunications is growing rapidly over time so that people's lifestyles also go hand in hand with the development of increasingly sophisticated technology causing people to follow a modern lifestyle, where people can make buying and selling transactions that used to occur in markets and supermarkets and until now buying and selling have appeared in the form of online buying and selling transactions using mobile phones and network assistance.  internet. This research aims to examine the advantages and disadvantages of buying and selling online and find the perspective of Majene Regency scholars about buying and selling online. This type of research is qualitative research. Data analysis is done by trying to describe the data that was collected, and from the data is drawn conclusions. This research was conducted in the district of Banggae Majene Regency and the speaker is a fiqh scholar domiciled in Banggae Subdistrict or works in one of the Agencies located in Majene Regency.The results of the research obtained that based on the perspective of the scholars of Banggae District Majene about online buying and selling, that the scholars of Banggae District of Majene Regency argue that the online buying and selling is valid or allowed as long as it runs in accordance with the rules of sale and selling online.  Buy in Islam and do not have elements that can cancel a transaction to buy and sell according to Islam. REFERENCES Abdurahman, dkk. (2010). Fiqih Muamalah, Jakarta: Prenada Media Group. Akbar Setiadi, Dkk, (2009). Metododologi Penelitian Sosial, Jakarta: PT Bumi Aksara Al-Fauzan Saleh, (2005). Fikih Sehari-hari, Jakarta: Gema Inani Press, Anwar Syaifuddin, (2001). Metode Penelitia, Yogyakarta: Pustaka Pelajar, Baits, Nur Ammi. (2018). Pengantar Permodalan Dalam Islam, Jogjakarta: Pustaka Muamalah Jogja, Baits, Nur Ammi. (2019). Pasar Muslim dan Dunia Makelar, Jogjakarta: Pustaka Muamalah Jogja, Baits, Nur Ammi. (2020). Pengantar Kaidah Fiqih Kubro dan Penerapannya Dalam Fiqh Muamalah, Jogjakarta: Pustaka Muamalah Jogja. Baits, Nur Ammi. (2021). Halal Haram Bisnis Online, Jogjakarta: Muamalah Publishing. Basyir, Ahmad Azhar, (1982). Asas-Asas Hukum Muamalat, Yogyakarta: UII Pres, Bakti, Muhammad Nur, (2015).Majene dalam Angka Majene In Figures Majene: Badan Pusat Statistik Kabupaten Majene. Davies Leslie, dkk, (1999). Kamus Lengkap Ekonomi, Jakarta: Erlangga, Danim, Sudarwan. (2002). Menjadi Peneliti Kualitatif, Bandung: CV Pustaka Setia. Diana Anastasia, (2001). Mengenal E-Business, Yogyakarta: Andi Offset. Ghazaly, Abdul Rahman, (2010). Fiqh Muamalat, Jakarta: Kencana. Haeron Nasrun. (2007). Fikih Muamalah, Jakarta: Gaya Media Pratama Jakarta. Ikid, Dkk. (2018). Jual Beli Dalam Perspektif Ekonomi Islam, Yogyakarta: Penerbit Gava Media. Edwin, Mustafa, Dkk. (2009). Pengenalan Ekslusif Ekonomi Islam, Jakarta. Kencana. Faisal, Sanapia. (2000). Penelitian Kualitatif, Dasar-Dasar dan Aplikasi, Malang: Yayasan Asih Asah Asuh, Hasan, Akhmad Farroh. (2018). Fikih Muamalah Dari Klasik Hingga Kontemporer, Malang: UIN Malang Press.  Hasanuddin M, OniSahroni, (2020). Fikih Muamalah Teori Dinamika Akad dan Implementasinya dalam Ekonomi Syariah, Cet. IV; Depok: PT. Raja Grafindo Persada. Hasan M. Ali, (2003). Berbagai Macam Transaksi dalam Islam, Fiqih Muamalah, Jakarta: PT. Raja Grafindo Persada, Husain dan Setiady Akbar. (2009). Metodologi Penelitian Sosial. Cet. II; Jakarta: PT. Bumi Aksara http://eprints.ums.ac.id/27087/ http://almanhaj.or.id/9478-muamalah-dengan -0rang-kafir.hml. http://humas.majenekab.go.id/profil-majene/             Kementerian Agama Republik Indonesia. Al-Qur’an dan Terjemahnya, Bandung: Diponegoro, Mawardi Djalaluddin, (2021). Ulama Kabupaten Majene, Wawancara, Majene 05 Juli. Maxmanroe, “3 Jenis Transaksi Jual Beli Online Terpopuler di Indonesia”, Blog Maxmanroe. https://www.maxmanroe.com/2014/01/ 3-jenis-transaksi-jual-beli-online-terpopuler-di indonesia. html Meleong Lexy J. (2006). Metodologi Penelitian kualitatif, Edisi Revisi, Bandung: PT. Rosda Karya, Muhajir Neong, (2001). Metodologi Penelitian Kualitatif, Yogyakarta: Rake Serasin. Muslich, Akmad Wahid, (2017). Fikih Muamalah, Cet. IV; Jakarta: Amzah, Nasution, (2008). Berbagai Pendekatan dalam Proses Belajar Mengajar, Bandung:  Bumi Aksara. Nazir Moh, (2005). Metode Penelitian, Bogor: Ghalia Indonesia, Peraturan Mahkamah Agung RI No. 2 Tahun 2008, Kompilasi Hukum Ekonomi Syariah (KHES), Buku II Rasjid Solaeman, (2007). Fiqih Islam, Bandung, Sinar Baru Algesindo, Rifa’i Moh. Terj Khulasoh al-Ahyar, Semarang: CV. Toha Putra.tt. Romndhon Riski Muhammad. (2015). Jual Beli Online Menurut Mazhab Syafi’i, Surabaya: CV. Garuma Mas Sejahtera. Saifulloh, Moh. (2005). Fiqi h Islam Lengkap, Surabaya. Terbit Terang. Sinaga Ali Imran, Nurhayati, (2019). Fiqh & Ushul Fiqh, Cet. II; Jakarta: Pranamedia Group. Shidiq Sapiudin, (2019). Fikih Kontemporer, Cet. III; Jakarta: Prena Media Group, Soemitra Andri, (2021). Hukum Ekonomi Syariah dan Fikih Muamalah di Lembaga Keuangan dan Bisnis Kontemporer, Cet.II; Jakarta: Kencana. Sudijono Anas, (2005). Evaluasi Pendidikan, Jakarta: PT Raja Grafindo Persada. Sugiyono. (2012). Metode Penelitian Pendidikan (Pendekatan Kuantitatif, Kualitatif dan R & D) Cet. XIV; Bandung: Alfabeta. Suhendi Hendi, (2010). Fiqh Muamalah, Cet. VI; Jakarta: PT Raja Grafindo Persada. Suryawati Siti Hajar. (2021). Analisis Potensi dan Peran Sektor Perikanan di Kabupaten Majene Provinsi Sulawesi Barat, Makassar UNHAS. Syafe’i, Rahmat. (2001). Fiqh Muamalah. Cet. X; Bandung; CV Pustaka Setia. www.majenekab.go.id